2009
DOI: 10.1097/ta.0b013e31818d0e43
|View full text |Cite
|
Sign up to set email alerts
|

Video Registration of Trauma Team Performance in the Emergency Department: The Results of a 2-Year Analysis in a Level 1 Trauma Center

Abstract: Video registration of diagnostic and therapeutic procedures by a multidisciplinary trauma team facilitates an accurate analysis of possible deviations from protocol. In addition to identifying technical errors, the role of the team leader can clearly be analyzed and related to team actions. Registration strongly depends on availability of video tapes, timely started registration, and hardware functioning. The results from this study were used to develop a training program for trauma teams in our hospital that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 11 publications
0
65
0
1
Order By: Relevance
“…Teams with a leader had higher rates of completion of their secondary survey and formulation of a plan than teams without an identified leader 5. In Lubbert et al, a lack of leadership led to more errors and delays in performing expected tasks during the primary and secondary surveys 6. In Capella, strong teamwork led to decreased time to computed tomography (CT), endotracheal intubation, and transfer to the operating room 7.…”
Section: Resultsmentioning
confidence: 99%
“…Teams with a leader had higher rates of completion of their secondary survey and formulation of a plan than teams without an identified leader 5. In Lubbert et al, a lack of leadership led to more errors and delays in performing expected tasks during the primary and secondary surveys 6. In Capella, strong teamwork led to decreased time to computed tomography (CT), endotracheal intubation, and transfer to the operating room 7.…”
Section: Resultsmentioning
confidence: 99%
“…11 In the emergency medicine speciality, it has been used to audit resuscitation, [12][13][14][15] including neonatal, 16,17 paediatric 18,19 and trauma resuscitation. 20,21 These studies continually highlight the clear educational and clinical benefits of such systems. They predominantly report the degree to which their clinical practice rates have improved, but there is often little-to-no explanation of system set-up.…”
Section: Introductionmentioning
confidence: 99%
“…6 When compared with traditionally available methods to detect management errors, that is, medical record review, video recording has been shown to be more effective. 5 Systematic video reviews have the potential of improving trauma care, 7 and various "video audit" approaches have been recommended.…”
Section: Discussionmentioning
confidence: 99%